Supplementation of Lactobacillus plantarum ATCC14917 mitigates non-alcoholic fatty liver disease in high-fat-diet-fed rats - Wen, Xingjian; Liu, Hejing; Luo, Xiaoling; Lui, Li; Fan, Jiuyu; Xing, Yajing; Wang, Jia; Qiao, Xingfang; Li, Na; Wang, Guixue (Frontiers in Microbiology, 2023)
Atherosclerosis and non-alcoholic fatty liver disease (NAFLD) have been increasing at an alarming rate worldwide. Many clinical studies have underlined the link between NAFLD and atherosclerosis. Our previous experiments have discovered that Lactobacillus (L.) plantarum ATCC14917 supplementation could decrease the progression of atherosclerotic lesion formation. In this study, we aimed to investigate the role of supplementation of L. plantarum ATCC14917 mitigates liver injury in rats fed with a high-fat diet (HFD, 45% kcal from fat). A total of 32 rats were randomly divided into four groups, including two intervention groups, who fed with HFD and administering either 1 × 107 or 1 × 109 colony forming units (CFU) of L. plantarum ATCC14917, the normal control group, and the HFD control group. The results showed that supplementation with low-dose and high-dose of L. plantarum ATCC14917 for 8 weeks could alleviate the body weight gain (P < 0.05), hepatic steatosis, and serum lipid metabolism (P < 0.05) in HFD-fed rats. Moreover, supplementation of L. plantarum ATCC 14917 decreased total cholesterol (TC), triglyceride (TG), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels (P < 0.05) in serum, and improved HFD-associated inflammation (P < 0.05). Furthermore, cecal contents were analyzed by high-throughput 16S ribosomal RNA sequencing. The results indicated that supplementation of L. plantarum ATCC 14917 could ameliorate HFD-induced gut dysbiosis. In summary, our findings suggest that supplementation of L. plantarum ATCC 14917 could mitigate NAFLD in rats, suggesting it may be considered as a probiotic agent for preventing HFD-induced obesity.